2022
DOI: 10.1111/dom.14682
|View full text |Cite
|
Sign up to set email alerts
|

Acute changes in plasma glucose increases left ventricular systolic function in insulin‐treated patients with type 2 diabetes and controls

Abstract: Aims We aimed to evaluate the effect of acute hyperglycaemia and hypoglycaemia on cardiac function in patients with type 2 diabetes (T2D) and a control group. Materials and methods In a nonrandomized interventional study, insulin‐treated patients with T2D (N = 21, mean ± SD age 62.8 ± 6.5 years, body mass index [BMI] 29.0 ± 4.2 kg/m2, glycated haemoglobin [HbA1c] 51.0 ± 5.4 mmol/mol [6.8 ± 0.5%]) and matched controls (N = 21, mean ± SD age 62.2 ± 8.3 years, BMI 29.2 ± 3.5 kg/m2, HbA1c 34.3 ± 3.3 mmol/L [5.3 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In support of the present result, another study by Aygün et al [8] found increase in heart rate during acute hyperglycemic crisis more than heart rate after recovery. Additionally, the study of Andersen et al [14] supported the same result of the faster heart rate at the time of acute hyperglycemic syndromes.…”
Section: Discussionmentioning
confidence: 74%
“…In support of the present result, another study by Aygün et al [8] found increase in heart rate during acute hyperglycemic crisis more than heart rate after recovery. Additionally, the study of Andersen et al [14] supported the same result of the faster heart rate at the time of acute hyperglycemic syndromes.…”
Section: Discussionmentioning
confidence: 74%
“…Finally, the present study does not include a nondiabetic control group. However, a previous study indicates similar cardiac function changes in patients with type 2 diabetes and matched controls 27 …”
Section: Discussionmentioning
confidence: 84%
“…However, a previous study indicates similar cardiac function changes in patients with type 2 diabetes and matched controls. 27 The primary strength of the study is that the effects of hypoglycaemia and subsequent recovery in both hyperglycaemia and euglycaemia were successful, well-controlled and assessed in the same participant. Thus, we could compare the difference individually and limit potential confounding.…”
Section: Discussionmentioning
confidence: 99%